POSSIBILITY OF ANGIOTENSIN RECEPTOR BLOCKERS IN OPTIMIZING OF ANTIHYPERTENSIVE PHARMACOTHERAPY IN PATIENTS AFTER STROK - Z M. Sizova (Рациональная фармакотерапия в кардиологии)
Current possibilities of AT1 receptor blockers (ARBs), such as candesartan, for optimization of antihypertensive therapy in stroke patients are presented in the article. ARBs are original drugs that effect to the delicate balance of pressor and depressor neurohormonal systems. They also have cerebroprotective action and are the drugs of choice for primary and secondary prevention of stroke in hypertensive patients